(untitled) - Cunningham, William P. (Boston, MA, 2004)
Rather than the 25 to 30 chapters found in most environmental science textbooks, the authors have limited Principles of Environmental Science: Inquiry and Applications to 15 chapters--perfect for the one-semester, non-majors environmental science course. True to its title, the goal of this concise text is to provide an up-to-date, introductory view of essential themes in environmental science along with offering students numerous opportunities to practice scientific thinking and active learning
Keywords: Environmental sciences